HUBUNGAN USIA, TINGKAT PENDIDIKAN, DAN GENDER PEMILIK UMKM TERHADAP PROGRAM UMKM GO DIGITAL DI KABUPATEN GRESIK - Tikno Tikno; Putri Amelia (JURNAL TEKNOLOGIA, 2019)
The government of Indonesia supports the development of small and medium-sized enterprises (SMes) by providing many programs to accelerate their business. UMKM Go Digital is one of the program provides easier access for SMEs into digital market. However, the participation rate was relatively low as less than 5%. This research aims to investigate the problem by integrating two theories in technology adoption, which are the Task Technology Fit (TTF) and the Unified Theory of Acceptance and Use of Technology (UTAUT)-then developed as UTAUT2. The research model explains 84,5% and 88,7% variation in TTF and use behaviour of UMKM Go Digital, respectively. The result also confirms that age, gender and education level have not affected the adoption. Future research should consider to extend the originated-location of the SMEs and the number of the participants as well to gain more comprehensive results